Surgical Approaches in Management of Spinal Tuberculosis - Kumar, Vishal; Salaria, Amit Kumar; Aggarwal, Aditya; Dhatt, Sarvdeep Singh (Annals of the National Academy of Medical Sciences (India), 2021)
Although the management of spinal tuberculosis (TB) is mainly medical, there are select surgical interventions for the same, especially in the event of complications. However, with multiple choices with regard to approaches and surgical techniques, one is often left with too many options. We, therefore, performed a literature review on the subject with respect to the surgical approaches to control spinal TB. Our aim is to enable the reader to understand the rationale behind various surgical approaches and techniques involved in managing spinal TB.
Keywords: tuberculosis; approaches to control spinal TB; anti-tubercular treatment; functional outcome